The use of pollen cues in resource location by a pollinator and a pest - Cook, Samantha (2001)
This thesis presents evidence that pollen colour and odour may be used as cues in resource-location by pollen feeding insects; namely, the pollen beetle, Meligethes aeneus, a pest of cruciferous crops such as oilseed rape, Brassica napus (OSR), and the honey bee, Apis mellifera, an economically important generalist pollinator.